Systematic review of cardiovascular neurocristopathy—contemporary insights and future perspectives - Soliman, Osama; Acharya, Yogesh; Gilard, Martine; Duffy, Garry; Wijns, William; Kannan, Venkatesh; Sultan, Sherif (Frontiers in Cardiovascular Medicine, 2024)
Introduction Neural crest cells (NCCs) are multipotent and are attributed to the combination of complex multimodal gene regulatory mechanisms. Cardiac neural crest (CNC) cells, originating from the dorsal neural tube, are pivotal architects of the cardio-neuro-vascular domain, which orchestrates the embryogenesis of critical cardiac and vascular structures. Remarkably, while the scientific community compiled a comprehensive inventory of neural crest derivatives by the early 1980s, our understanding of the CNC's role in various cardiovascular disease processes still needs to be explored. This review delves into the differentiation of NCC, specifically the CNC cells, and explores the diverse facets of non-syndromic cardiovascular neurocristopathies. Methods A systematic review was conducted as per the PRISMA Statement. Three prominent databases, PubMed, Scopus, and Embase, were searched, which yielded 1,840 studies. We excluded 1,796 studies, and the final selection of 44 studies formed the basis of this comprehensive review. Results Neurocristopathies are a group of genetic disorders that affect the development of cells derived from the NC. Cardiovascular neurocristopathy, i.e., cardiopathy and vasculopathy, associated with the NCC could occur in the form of (1) cardiac septation disorders, mainly the aortico-pulmonary septum; (2) great vessels and vascular disorders; (3) myocardial dysfunction; and (4) a combination of all three phenotypes. This could result from abnormalities in NCC migration, differentiation, or proliferation leading to structural abnormalities and are attributed to genetic, familial, sporadic or acquired causes. Discussion Phenotypic characteristics of cardiovascular neurocristopathies, such as bicuspid aortic valve and thoracic aortic aneurysm, share a common embryonic origin and are surprisingly prevalent in the general population, necessitating further research to identify the underlying pathogenic and genetic factors responsible for these cardiac anomalies. Such discoveries are essential for enhancing diagnostic screening and refining therapeutic interventions, ultimately improving the lives of individuals affected by these conditions.